Study on Marketing Strategies of Graduate Entrance Examination Training Business - Taking New Oriental Online Jinan Branch as an Example - Kuan, Xin; Chollathanratanapong, Jidapa (Asia Pacific Journal of Religions and Cultures, 2024)
The purpose of this study were : 1) To analyze the current situation of postgraduate entrance examination training at New Oriental Online Jinan Branch by SWOT analysis; 2) To improve the marketing strategy of New Oriental Online Jinan Branch's postgraduate entrance examination training business through 4P theory. This paper is based on the 4P marketing mix theory and adopts a quantitative research method to conduct a questionnaire survey on 300 students both inside and outside the Jinan branch of New Oriental Online. Then, the 4P marketing theory is sorted out and an interview outline is written. Through analysis, this paper finds that: 1) New Oriental Online Jinan Branch's brand influence is insufficient and industry competition is becoming increasingly fierce; 2) We need to further enrich and optimize the courses and pricing system related to postgraduate entrance examination training at New Oriental Online Jinan Branch, improve marketing strategies, and expand marketing channels to meet the training needs of various postgraduate students and promote the efficient development of the company.